2007
DOI: 10.1007/bf02993958
|View full text |Cite
|
Sign up to set email alerts
|

A new pyrrole alkaloid isolated fromArum palaestinum Boiss. and its biological activities

Abstract: The phytochemical analysis of the ethyl acetate fraction of Arum palaestinum Boiss. (Araceae) led to the isolation and identification of a new polyhydroxy alkaloid compound; (S)-3,4,5-trihydroxy-1 H-pyrrol-2(5H)-one (1), and other five known compounds; caffeic acid (2), isoorientin (3), luteolin (4) and vicenin 11 (5), as well as the rare compound 3,6,8-trimethoxy, 5,7,3',4'-tetrahydroxy flavone (6). The structural elucidations of all the compounds were based on spectroscopic data (1H- and 13C-NMR, DEPT, HSQC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 14 publications
1
25
0
Order By: Relevance
“…The antioxidant capacity of these compounds was carried out by determination photometrically through their scavenging activity against the stable artificial free radical, 1,1-diphenyl-2-picrylhydrazyl (DPPH•), using the method as described previously (El-Desouky et al, 2007) with slight modification. In brief, 200 μL of 0.208 mM DPPH solution (in ethanol) was added to an Eppendorf tube containing a 200 μL aliquot of different concentrations sample (in water).…”
Section: Dpph• Scavenging Capacitymentioning
confidence: 99%
“…The antioxidant capacity of these compounds was carried out by determination photometrically through their scavenging activity against the stable artificial free radical, 1,1-diphenyl-2-picrylhydrazyl (DPPH•), using the method as described previously (El-Desouky et al, 2007) with slight modification. In brief, 200 μL of 0.208 mM DPPH solution (in ethanol) was added to an Eppendorf tube containing a 200 μL aliquot of different concentrations sample (in water).…”
Section: Dpph• Scavenging Capacitymentioning
confidence: 99%
“…But the isolation and characterization of these compounds from Arum started relatively late. 89 The polyhydroxy alkaloid that was isolated in the same year, 90 provides an interesting starting material for synthetic purposes. Two other new alkaloids were reported later, and they have even simpler structures.…”
Section: Figure 3 Structures Of T-cadinol and T-muurololmentioning
confidence: 99%
“…But studying other reports show that this compound is present in A. palaestinum, and many of its derivatives. 90 …”
Section: Figure 3 Structures Of T-cadinol and T-muurololmentioning
confidence: 99%
“…Fifty-six compounds were identified from the odour of A. maculatum. The major components being: 2-heptanone, indole, p.cresol, Also, several ketones and esters were detected and the majority of the compounds were terpenoids [8]. By reviewing the available literature, it was found nothing about the chemical constituents of the volatiles from the flowers of Arum cyrenicum so the aim of this study is the isolation and identification of volatile constituents from the Arum cyrenicum flowers using solvent extraction.…”
Section: Introductionmentioning
confidence: 97%
“…The phytochemicals like volatile oil, terpenes, flavonoids, lectins and alkaloids were studied in Arum genus. Kite et al [8][9][10] studied the odours of many Arum species and they identified 36 compounds, in which butanoïc acid esters, 1-decene, terpenes (citronellene and its derivatives), p-cresol, methyl salicylate, indole and 2-heptanone are common compounds. Some species appear clearly different like A. creticum or A. palaestinum, whose rotten fruit odour is due to benzyl alcohol and ethyl acetate.…”
Section: Introductionmentioning
confidence: 99%